1975
DOI: 10.1152/ajplegacy.1975.228.1.196
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin and intestinal iron absorption: pancreatic enzymes and free iron

Abstract: Rat intestinal mucosa gave low yields of ferritin purified by standard procedures. The resulting ferritin had less protein relative to iron and migrated faster electrophoretically than ferritin from other rat tissues. Pancreatic duct ligation reduced these differences, suggesting digestive enzyme attack during ferritin isolation. Even in ligated rats, ferritin accounted for only 5-10% of mucosal iron. However, shortly after giving 59FeCl3 orally, 50% of mucosal radioactivity occurred in cell sap, about equally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

1978
1978
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 0 publications
1
7
0
2
Order By: Relevance
“…Although iron absorption was not measured directly, the increase of ferritin synthesis demonstrates that iron uptake had occurred. The observed increase of ferritin is in agreement with an earlier report that, in a time course similar to our studies following ingestion of 59 Fe, the ingested iron could be found in the enterocytes and in the liver (22). Since FPN1, as well as ferritin, contain an IRE in the 5Ј-untranslated region, iron ingestion should induce the IRP/IRE response to increase translation of both proteins.…”
supporting
confidence: 93%
“…Although iron absorption was not measured directly, the increase of ferritin synthesis demonstrates that iron uptake had occurred. The observed increase of ferritin is in agreement with an earlier report that, in a time course similar to our studies following ingestion of 59 Fe, the ingested iron could be found in the enterocytes and in the liver (22). Since FPN1, as well as ferritin, contain an IRE in the 5Ј-untranslated region, iron ingestion should induce the IRP/IRE response to increase translation of both proteins.…”
supporting
confidence: 93%
“…Thus, the weanling rats were in the process of estab lishing hepatic iron reserves and, therefore, the demand for dietary iron would be high and efficient iron absorption at the gastro intestinal tract paramount. The adult rats, on the other hand, with substantial iron reserves at the beginning of the period of experimental feeding would have required a small dietary supply of iron in order to maintain iron bal ance [7], It is perhaps worth noting that the impact of riboflavin deficiency on the activ ity of mucosal FMN oxidoreductase was greatest in the weanling animals in which the activity in the deficient rats at day 35 repre sented only 6.6% of activity at day 14, and 3.2% of the activity in the control animals, whereas in the adult deficient animal on day 49 enzyme activity was 27.9% of that at day 14 and 22.3% of control activity.…”
Section: Discussionmentioning
confidence: 99%
“…De spite extensive research into the mechanisms of iron absorption and a wealth of publica tions on the subject, a generally accepted mechanism for iron absorption has not yet been presented [2,14,15]. Recent studies rel egate mucosal ferritin to the role of a 'reser voir' protein, the iron in which is considered to be lost from the body with the sloughing off of the mucosal cell [8], although the pos sibility that iron in mucosal ferritin can still be made available to the blood need not be ruled out [7], The aim of the present study was not to tackle the complex subject of the mechanism for iron absorption but to estab lish whether riboflavin deficiency might im pair this process. The results show that both iron accumulation in rat pups and iron-mo bilising activity in gastro-intestinal mucosa are severely affected by riboflavin deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In intestinal cells, as in all cells, ferritin concentrations are regulated by iron dependent control of protein synthesis and degradation [21-23]. Data show that absorbed iron not exported from the enterocyte is stored in ferritin, but the recent awareness that, in solution at least, ferritin protein is a dynamic manager of iron, suggests the possibility of a dynamic role for ferritin during the process of intestinal iron absorption that has been little considered.…”
Section: Introductionmentioning
confidence: 99%